Noninvasive In Vivo Assessment of Cardiac Metabolism in the Healthy and Diabetic Human Heart Using Hyperpolarized 13C MRI. Issue 6 (13th March 2020) - Rider, Oliver J.; Apps, Andrew; Miller, Jack J.J.J.; Lau, Justin Y.C.; Lewis, Andrew J.M.; Peterzan, Mark A.; Dodd, Michael S.; Lau, Angus Z.; Trumper, Claire; Gallagher, Ferdia A.; Grist, James T.; Brindle, Kevin M.; et al.
Abstract : Rationale: The recent development of hyperpolarized 13 C magnetic resonance spectroscopy has made it possible to measure cellular metabolism in vivo, in real time. Objective: By comparing participants with and without type 2 diabetes mellitus (T2DM), we report the first case-control study to use this technique to record changes in cardiac metabolism in the healthy and diseased human heart. Methods and Results: Thirteen people with T2DM (glycated hemoglobin, 6.9±1.0%) and 12 age-matched healthy controls underwent assessment of cardiac systolic and diastolic function, myocardial energetics ( 31 P-magnetic resonance spectroscopy), and lipid content ( 1 H-magnetic resonance spectroscopy) in the fasted state. In a subset (5 T2DM, 5 control), hyperpolarized [1- 13 C]pyruvate magnetic resonance spectra were also acquired and in 5 of these participants (3 T2DM, 2 controls), this was successfully repeated 45 minutes after a 75 g oral glucose challenge. Downstream metabolism of [1- 13 C]pyruvate via PDH (pyruvate dehydrogenase, [ 13 C]bicarbonate), lactate dehydrogenase ([1- 13 C]lactate), and alanine transaminase ([1- 13 C]alanine) was assessed. Metabolic flux through cardiac PDH was significantly reduced in the people with T2DM (Fasted: 0.0084±0.0067 [Control] versus 0.0016±0.0014 [T2DM], Fed: 0.0184±0.0109 versus 0.0053±0.0041; P =0.013). In addition, a significant increase in metabolic flux through PDH was observed after the oral glucose challenge ( P <0.001). As is characteristic of diabetes mellitus, impaired myocardial energetics, myocardial lipid content, and diastolic function were also demonstrated in the wider study cohort. Conclusions: This work represents the first demonstration of the ability of hyperpolarized 13 C magnetic resonance spectroscopy to noninvasively assess physiological and pathological changes in cardiac metabolism in the human heart. In doing so, we highlight the potential of the technique to detect and quantify metabolic alterations in the setting of cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.